2021
DOI: 10.1186/s12993-021-00184-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in spatial learning and memory and hippocampal long-term potentiation at perforant pathway-dentate gyrus (PP-DG) synapses in Wistar rats

Abstract: Background Recent studies show that gender may have a significant impact on brain functions. However, the reports of sex effects on spatial ability and synaptic plasticity in rodents are divergent and controversial. Here spatial learning and memory was measured in male and female rats by using Morris water maze (MWM) task. Moreover, to assess sex difference in hippocampal synaptic plasticity we examined hippocampal long-term potentiation (LTP) at perforant pathway-dentate gyrus (PP-DG) synapses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 88 publications
(112 reference statements)
0
15
2
Order By: Relevance
“…In the case of MWM reference memory, we did not observe a sex difference between VPA-exposed male and female offspring. However, here and in our previous study ( Safari et al, 2021 ), we saw a sex difference between male and female control rats. Both IT and CT exercises in both control and VPA-exposed male rats significantly improved MWM acquisition.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In the case of MWM reference memory, we did not observe a sex difference between VPA-exposed male and female offspring. However, here and in our previous study ( Safari et al, 2021 ), we saw a sex difference between male and female control rats. Both IT and CT exercises in both control and VPA-exposed male rats significantly improved MWM acquisition.…”
Section: Discussioncontrasting
confidence: 62%
“…In our previous work ( Safari et al, 2021 ), we discussed the underlying mechanisms for sex differences in male and female control animals (male control rats outperformed female control rats). However, here we found that VPA-exposed female offspring had a better performance than VPA-exposed male offspring (unlike control animals where male offsprings performed better).…”
Section: Discussionmentioning
confidence: 99%
“…The greater normalized LTP in adult male than adult female rats ( Supplemental Figure S2 ) replicates Maren 12 . Higher levels of excitability in the MPP circuit of female rats than male rats are seen in data sets from earlier studies 13 (raw data shared by Safari and Karimi 2021), but see 14 for counter example.…”
Section: Resultsmentioning
confidence: 94%
“…The open field test was used to measure the locomotion function based on their spontaneous exploratory behavior in an open field maze ( Figure 2 A) [ 19 , 20 ]. The female Prdx6 −/− mice showed no significant difference in the total distance traveled ( Figure 2 B) [ U = 25, p = 0.171] and moving speed ( Figure 2 C) [ t 16 = 1.614, p = 0.126] compared with Prdx6 +/+ mice after 10 min of exploration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it appears to regulate emotional response and spatial memory formation in male mice [ 8 ]. Therefore, whether the Prdx6 gene influences stress-coping mechanisms [ 17 , 18 ] and memory performance [ 19 ] in females is intriguing. Thus, in the present study, we investigated the function of PRDX6 in the synaptic and behavioral phenotypes of female mice.…”
Section: Introductionmentioning
confidence: 99%